Development of Ultra-High-Performance Silica Fume-Based Mortar Incorporating Graphene Nanoplatelets for 3-Dimensional Concrete Printing Application - Salah H.A.; Mutalib A.A.; Kaish A.B.M.A.; Syamsir A.; Algaifi H.A. (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Although the use of 3D printing in civil engineering has grown in popularity, one of the primary challenges associated with it is the absence of steel bars inside the printed mortar. As a result, developing 3D printing mortar with ultra-high compressive, flexural, and tensile strengths is critical. In the present study, an ultra-high-performance mortar incorporating silica fume (SF) and graphene nanoplatelets (GNPs) was developed for 3D printing application. The concrete mixture added SF to the concrete mixture in the range between 0% and 20%, while GNPs were added as a partial replacement by cement weight from 0.5% to 2%. The flowability and the machinal properties of the proposed mortar, including compressive (CS), tensile (TS), and flexural strength (FS), were investigated and assessed. Microstructure analysis involving FESEM and EDX was also investigated and evaluated, while response surface methodology (RSM) was considered to predict and optimize the optimum value of GNPs and SF. Workability results show that the flowability is reduced when the amount of graphene increases. Based on the predicted and experimental results, ultra-high-strength mortar can be developed by including 1.5% of GNPs and 20% of SF, in which the CS jumped from 70.7 MPa to 133.3 MPa at the age of 28 days. The FS and TS were 20.66 MPa and 14.67 MPa compared to the control mix (9.75 MPa and 6.36 MPa), respectively. This favorable outcome was credited to the pozzolanic activity of SF and the effectiveness of GNPs in compacting the pores and bridging the cracks at the nanoscale level, which were verified by FE-SEM and EDX. In addition, the developed quadratic equations proved their accuracy in predicting and optimizing the mechanical properties with low error (less than 0.09) and high correlation (R2 > 0.97). It can be concluded that the current work is an important step forward in developing a 3D printing mortar. The lack of reinforcement in the printed mortar structure has been a considerable difficulty, and the SF and GNPs have increased the compressive, flexural, and tensile strengths of the mortar. Thus, these improvements will encourage the industry to utilize sustainable materials to produce more affordable housing. 2023 by the authors.